PENDAMPINGAN PEMASARAN DARING, KOREKSI DAN DIGITALISASI LOGBOOK PADA KARYAWAN SINAR PUTRA PERTAM BANTUL: Online Marketing Assistance, Logbook Correction And Digitalization To Sinar Putra Pertam Bantul Employees - Fikri Farhan; Guruh Ghifar Zalzalah; Adhi Prakosa (Pakis Journal Institute, 2023)
Indonesia's subsidized LPG gas distribution system is a closed system. Only certain entities can become agents and sub-agents. Each entity is supervised and required to make a report regarding the distribution of LPG gas. One form of this report is the logbook. Logbook is a crucial document. However, there are still problems related to logbooks that need to be more suitable, and logbooks in physical files are prone to damage and loss. Another problem for gas agents is selling non-subsidized gas, which needs to reach the sales target. Therefore this service activity aims to assist partners in correcting and digitizing logbook files. In addition, the research aims to increase public awareness regarding NPSO gas through online marketing assistance via social media. The methods used in this service activity are interviews and participatory learning. The results of this service show that logbooks that were previously not following regulations have been appropriately corrected, and logbook files that were previously still in physical form have been converted into digital form. In addition, social media marketing increases consumer awareness of NPSO gas.